Management of Severe Localized Periodontal Destruction Associated with A Cemental Defect: A Case Report - Nik Azis, Nik Madihah; Mohd, Nurulhuda (UI Scholars Hub, 2022)
This case involved the management of a possible cemental tear, which resulted in poor response to nonsurgical periodontal therapy. This case was managed by exploratory surgery, along with the intention to surgically reduce the periodontal pocket. Exploratory surgery revealed a localized cemental defect. The periodontium healed with pocket closure after exploratory surgery and open-flap debridement. The difficulty in clinically diagnosing a localized periodontal destruction and the lack of consensus on managing these cases were highlighted. The possibility of an undiagnosed cemental defect in a tooth with localized periodontitis should be considered in cases not responding to periodontal therapy.